Possibilities for Using TAM and Technology Frames Models to Assess the Acceptance of New Technologies in the Chilean Higher Education Quality Assurance - Luis González-Bravo; Maruzzella Valdivia-Peralta (Universidad Nacional, Costa Rica, 2015)
This essay reviews the importance of assessing the degree of acceptance of new technologies in the Chilean higher education institutions, as an input for managing quality assurance. Technology Acceptance and Technology Frames models are described, emphasizing their benefits in this field. Understanding and facilitating the process of new technologies acceptance in the organizations, by identifying those elements which hinder it, allows improving the implementation of quality assurance mechanisms in order to make the educational process more efficient and effective.